The Foreign Exchanges - Pigou, A. C. (Quarterly Journal of Economics, 1922)
Kate of exchange between two moneys part of a larger problem, 52. — Conditions requisite to equilibrium of exchange, 53. — Exceptions (1) government control, (2) monopoly, 54. — Connection between different commodities in international exchange, 56. — The effect of inconvertible paper, 62. — Purchasing power parities, 63. — Lapses from alignment between actual and normal rates of exchange, 70.